If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7+8x-19=15+3(x-17)
We simplify the equation to the form, which is simple to understand
-7+8x-19=15+3(x-17)
Reorder the terms in parentheses
-7+8x-19=15+(+3x-51)
Remove unnecessary parentheses
-7+8x-19=+15+3x-51
We move all terms containing x to the left and all other terms to the right.
+8x-3x=+15-51+7+19
We simplify left and right side of the equation.
+5x=-10
We divide both sides of the equation by 5 to get x.
x=-2
| 5/m=8/6 | | 2[t+6]-1=9 | | 3/n=10/7 | | x+8(12-x)=7x-(5x-42) | | 6/a=5/7 | | -16=-4[v+3] | | 1/2-3x=-1/2 | | -4+5x=36 | | x+8(12-x)=7x(5x-42) | | -8x-5x-96=60 | | 8/3=n/4 | | x-7x-61=23 | | 7=2[r+6]-5 | | r(x)=x(13-0.04x) | | -15=10+5v | | -2x-10+3x=9 | | 62=-7v-1 | | 2[w+2]=10 | | 9x^4/3x^3 | | 3a-1/6-1-4a/12=1 | | 37=7+6x | | 40*x*52=31500 | | (40*x)+52=31500 | | 2n+25=5n+15 | | -x-7x-94=34 | | (40*x)*50=31500 | | -3(3p+6)-2(3-14p)=3(8+6p) | | 3(3-9y)= | | 7=7-7x | | 4m+10=-18 | | -75-5x-7x=81 | | 7/2a*5/a^2 |